Tensile creep mechanical behavior of periodontal ligament: A hyper-viscoelastic constitutive model. (August 2021) - Zhou, Jinlai; Song, Yang; Shi, Xue; Zhang, Chunqiu
Highlights: A hyper-viscoelastic coupling modeling framework is proposed to describe nonlinear viscoelastic materials, two coupling modeling methods with limitations are excluded. The hyperelastic model and the nonlinear viscoelastic model were coupled for the first time to characterize the biomechanical behavior of periodontal ligament. For the first time, the creep law of periodontal ligament was clarified. A method to determine the initial point of creep curve is proposed. Abstract: Objective: In orthodontic treatment, the biomechanical response of periodontal ligament (PDL) induces tooth movement. Coupling modeling of PDL can effectively reflect its biomechanical response. The nonlinear creep mechanical behavior of PDL was studied by uniaxial tensile creep test and a new hyper-viscoelastic constitutive model. Two coupling modeling methods with limitations were excluded. Methods: PDL specimens were prepared from the central incisors of pig mandible. The theoretical step function was replaced by static loading with a total loading time of 1 s. The creep loading with the constant stresses of 0.05, 0.1, and 0.15 MPa was selected and kept unchanged for 1000 s. The instantaneous hyperelastic mechanical behavior and time-dependent nonlinear viscoelastic mechanical behavior of PDL were characterized by coupled instantaneous third-order Ogden hyperelastic and time-dependent nonlinear creep models. Results: The results showed that the instantaneous elastic curve of PDL increases in the form of hyperelastic index. The creep strain and creep compliance curves increase rapidly before 200s, and then increase slowly in steady state. The creep strain increased with an increase in the constant stress; conversely, the creep compliance decreased with an increase in the constant stress. The results showed that the experimental data were highly consistent with the hyper-viscoelastic constitutive model (R 2 >0.97). Significance: We normalize the framework of hyper-viscoelastic coupling modeling (Instantaneous hyperelastic model + time-dependent nonlinear viscoelastic model). Which can be extended to other nonlinear viscoelastic biomaterials.